Odontological-anthropological investigation of gypsies from Bulgaria - Minkov, Cvetan B. (Anthropological Review, 1977)
Six odontological characters were examined on three groups of Gypsies: 1. muslimans from Sofia (106), muslimans from Sliven (111) and christians from Sliven (107). It was observed occurence of: lower M1 with six cusps, lower M1 with four cusps, lower M2 second molars with four cusps, distal crest of trigonid, genuform fold metaconid and termination of 2med groove in II groove (three last characters were observed on lower first molar). Results of investigations may be summarized as follows: 1. There are no significant differences between the groups examined, so they belong to the same breeding population. 2. Frequencies of traits occuring among the Gypsies enable to include them into so called western odontological Stock (according to Zubov 1973).